Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{12}{20}\)= \(\frac{6}{10}\)= \(\frac{3}{5}\)
\(\frac{3}{4}\)= \(\frac{9}{12}\)= \(\frac{12}{16}\)= \(\frac{15}{20}\)
\(\frac{75}{45}\)= \(\frac{15}{9}\)= \(\frac{5}{3}\)
\(\frac{3}{4}\)= \(\frac{18}{24}\)= \(\frac{12}{16}\)
12/20 = 6/10 = 3/5
3/4 = 9/12 = 12/16 = 15/20
75/45 = 15/9 = 5/3
3/4 = 18/24 = 12/16
Tk mk nha
12/14 + 15/20 + 6/7 + 3/4
= ( 12/14 + 6/7 ) + ( 15/20 + 3/4 )
= ( 6/7 + 6/7 ) + ( 3/4 + 3/4 )
= 12/7 + 6/4
= 48/28 + 42/28
= 90/28
= 45/14
Tham khảo nha !!!
\(\frac{1}{2}:\frac{3}{2}:\frac{5}{4}:\frac{6}{5}:\frac{7}{6}:\frac{8}{7}\)
\(=\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{4}{5}\cdot\frac{5}{6}\cdot\frac{6}{7}\cdot\frac{7}{8}\)
\(=\frac{1\cdot\left(2\cdot5\cdot6\cdot7\right)}{8\cdot3\cdot\left(2\cdot5\cdot6\cdot7\right)}\)
\(=\frac{1}{24}\)
\(\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{3}{4}\cdot\frac{4}{5}\cdot\frac{5}{6}\cdot\frac{6}{7}\cdot\frac{7}{8}\cdot\frac{8}{9}\cdot\frac{9}{10}\)
\(=\frac{1\cdot\left(2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9\right)}{\left(2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9\right)\cdot10}\)
\(=\frac{1}{10}\)
a) \(\frac{27}{36}=\frac{3}{4}\)
b) \(\frac{45}{60}=\frac{3}{4}\)
c) \(\frac{2}{4}=\frac{1}{2}\)
d) \(\frac{10}{12}=\frac{5}{6}\)
e) \(\frac{112}{252}=\frac{4}{9}\)
Đúng nha bạn !!@@
\(\frac{1}{3}+\frac{3}{4}x\frac{5}{9}=\frac{1}{3}+\frac{5}{12}=\frac{3}{4}\)
\(\frac{7}{12}-\frac{5}{4}x\frac{2}{15}=\frac{7}{12}-\frac{1}{6}=\frac{5}{12}\)
\(y+\frac{1}{4}=\frac{7}{8}-\frac{3}{8}=y+\frac{1}{4}=\frac{1}{2}=\frac{1}{2}-\frac{1}{4}=\frac{1}{4}\)
\(y-\frac{5}{12}=\frac{2}{3}-\frac{1}{4}=y-\frac{5}{12}=\frac{5}{12}=\frac{5}{12}+\frac{5}{12}=\frac{5}{6}\)
\(\frac{12}{7}xy=\frac{16}{21}=\frac{16}{21}:\frac{12}{7}=\frac{4}{9}\)
\(\frac{5}{4}:y=\frac{7}{12}=\frac{5}{4}:\frac{7}{12}=\frac{15}{7}\)
12/5 -4/5 =8/5
11/6 -2/3 =21/18 =7/6
7/8 -2/7 =33/56
4 -8/5 =20/5-8/5 =12/5
2 -3/8 =16/8 -3/8 =13/8
16/7 -2 =16/7 -14/7 =2/7
25/4 -3=25/4 -12/4 =13/4
câu 2 : câu 3 :
a) 8/5 a)4 - 8/5 = 20/5 - 8/5 =12/5
b) 7/6 b)2 - 3/8 =16/8 - 3/8 = 13/8
c) 35/56 c)16/7 - 2 = 16/7 - 14/7 = 2/7
d)25/4 - 3 = 25/4 - 12/4 = 13/4
1 + 1 = 2
1 + 9 = 10
4 + 5 = 9
\(\frac{15}{16}-\frac{7}{16}=\frac{8}{16}=\frac{1}{2}\)
\(\frac{12}{9}-\frac{1}{4}=\frac{48}{36}-\frac{9}{36}=\frac{39}{36}=\frac{13}{12}\)
\(\frac{18}{27}-\frac{2}{6}=\frac{36}{54}-\frac{18}{54}=\frac{18}{54}=\frac{1}{3}\)
\(\frac{37}{12}-3=\frac{37}{12}-\frac{36}{12}=\frac{1}{12}\)
\(5-\frac{14}{3}=\frac{15}{3}-\frac{14}{3}=\frac{1}{3}\)
\(\frac{24}{36}-\frac{6}{12}=\frac{8}{12}-\frac{6}{12}=\frac{2}{12}=\frac{1}{6}\)
\(1+\frac{2}{3}=\frac{3}{3}+\frac{2}{3}=\frac{5}{3}\)
\(\frac{3}{4}-\frac{2}{7}=\frac{21}{28}-\frac{8}{28}=\frac{13}{28}\)